Double-layer metal mesh etched by femtosecond laser for high-performance electromagnetic interference shielding window. Issue 39 (17th July 2019) - Zhang, Yaqiang; Dong, Hongxing; Li, Qisong; Mou, Nanli; Chen, Lulu; Zhang, Long
Abstract : An excellent transparent EMI shielding window is proposed and demonstrated theoretically and experimentally. The results show that the SE reaches over 37.61 dB at 150 MHz to 5 GHz, while the average visible transmittance remains at ∼76.35%. Abstract : An excellent transparent electromagnetic interference (EMI) shielding window is proposed and demonstrated theoretically and experimentally. The window is composed of double layers of Au–Ni composite mesh, separated by the quartz-glass substrate. The simulation exhibits that the shielding effectiveness (SE) of the double-layer mesh can be improved by increasing the thickness of the substrate in the low frequency range far below the first interfere valley. The measured SE of the proposed structure reaches over 37.61 dB covering an ultra-wide frequency ranging from 150 MHz to 5 GHz, with a maximal SE of 75.84 dB at 3.58 GHz, while the average optical transmittance of the double-layer mesh maintains ∼76.35% at 400–900 nm. Moreover, femtosecond laser direct writing processing technology is used to manufacture the double-layer metal grids, the fabricated grids are not easy to be scuffed off and has a longer operating life. Such a high-performance EMI shielding window has great potential applications in precision optical monitoring instrument and military devices.